Effect of polyethylene terephthalate (PET) and polypropylene (PP) fibers on the shear behavior of RC deep beams - Ramhormozy, Ali; Kazeminezhad, Ehsan; Safakhah, Soroush (Revista de la Construcción. Journal of Construction, 2023)
Today, environmental health needs more attention than in the past. Objects consisting of plastic materials such as bottles take many years to decompose. Therefore, in the recent years, a lot of research has been done to reuse them and one of which is use in the concrete mixes. In previous research, very low percentages of these materials (between 0.5% and 1.5%) has been used as fine aggregate substitutes in the concrete and evaluations have more focused on the flexural strength. In this research, Polyethylene terephthalate (PET) as a substitute for sand and Polypropylene fibers (PP) as an additive material are used in the concrete mixes. 14 concrete beams in both reinforced and unreinforced states have been evaluated. The replacement percentage of the PET is 10, 30 and 60% and additive percentage of the PP is 0.5, 1.5 and 3% of the total weight of concrete. The dimensions of the beams have been chosen in such a way to categorized in the deep beams. So, rectangular cross-section has been considered (width = 100mm and height = 400mm). Shear strength and ductility are two important parameters that have been evaluated in this research.